Effects of Incorporating Clinoptilolite in Colostrum on the Immunity and Diarrhoea in Newborn Calves - Adina-Mirela Ariton; Andra-Sabina Neculai-Văleanu; Ioana Poroșnicu (Scientific Papers Animal Science and Biotechnologies)
Clinoptilolite, a naturally occurring zeolite present in sedimentary rock, has significant potential as an essential component for the removal of toxins inside the gastrointestinal system. Its detoxifying, antioxidant, haemostatic, anti-diarrheic, growth-promoting, and immunostimulant characteristics render it very applicable in animal biotechnology and veterinary medicine. In recent years, clinoptilolite has become more popular in animal nutrition, particularly for its ability to enhance performance and promote overall health. Diarrhoea in neonates is a very widespread ailment that leads to significant mortality rates and cost ramifications. Bovine colostrum plays a crucial role in the early feeding of calves, and the incorporation of clinoptilolite into colostrum has been shown to reduce the likelihood of diarrhoea syndrome. Clinoptilolite-based products are being used more often in the fields of veterinary and human medicine due to their beneficial features, such as their capacity to facilitate ion exchange and adsorption. The objective of the study was to examine the characteristics of clinoptilolite included into colostrum in neonatal calves, specifically focusing on its impact on immunity and the occurrence of diarrhoea.